An 8 K elastocaloric temperature change induced by 1.3% transformation strain in Ni44Mn45 − xSn11Cux alloys. (15th March 2017) - Li, Yang; Sun, Wen; Zhao, Dewei; Xu, Hui; Liu, Jian
Abstract: The influence of Cu substitution for Mn on martensitic transformation, superelasticity and associated elastocaloric effect in Ni44 Mn45 − x Sn11 Cu x ( x = 0–4) magnetic shape memory alloys has been investigated. The transformation temperatures were tuned around room temperature by increasing the Cu content. Ni44 Mn41 Sn11 Cu4 exhibits a giant adiabatic cooling of − 8 K at a small transformation strain of 1.3%, indicating it as a promising candidate material for elastocaloric refrigeration. Graphical abstract: (a) Steady stress-strain curves cycled for seven times in Ni44 Mn41 Sn11 Cu4 at a low strain rate of 0.03% s − 1 . (b) Near adiabatic stress-strain curve of Ni44 Mn41 Sn11 Cu4 at a high strain rate of 3% s − 1 . (c) Corresponding temperature evolutions of specimen surface in-situ measured by an infrared camera during adiabatic compression test in (b). (d) Local temperature-time profile of the central position of specimen (white circle), as well as the average temperature-time profile of the entire detected surface extracted from (c).